A kinetic model for the photocatalytic reduction of CO2 to methanol pathways. (November 2019) - Abdullah, H; Khan, M M R; Yaakob, Z; Ismail, N A
Abstract: Carbon dioxide (CO2 ) is one of the greenhouse gases that contribute to global warming. CO2 could be converted to valuable products such as hydrocarbons through the photocatalytic process. The aim of this research was to develop the kinetic model for the photocatalytic reduction of CO2 to methanol (CH3 OH) in liquid phase reaction using cerium oxide-titanium dioxide (CeO2 -TiO2 ) catalyst. The Langmuir-Hinshelwood approach was used in developing rate laws for the catalytic reaction using the catalytic reaction mechanism proposed. The catalytic reaction mechanism is about the adsorption of reactant (CO2 dissolved in the liquid phase), the reaction on catalyst surface and desorption of product. The experimental kinetic data were evaluated in the Polymath 6.1 software. In this study, two types of mechanism are proposed whereas one is considered the carbon monoxide (CO) oxidation while the other is not. Based on the model fitting, it was found that the model considers the CO oxidation is fitted well with the experimental data represents that the oxidation reaction of intermediate product, CO is the rate-determining step in the photocatalytic reduction of CO2 to CH3 OH in liquid phase reaction.